2009
DOI: 10.1364/oe.17.002850
|View full text |Cite
|
Sign up to set email alerts
|

Frequency response in step index plastic optical fibers obtained from the generalized power flow equation

Abstract: We present a method to obtain the frequency response of step index (SI) plastic optical fibers (POFs) based on the power flow equation generalized to incorporate the temporal dimension where the fibre diffusion and attenuation are functions of the propagation angle. To solve this equation we propose a fast implementation of the finite-difference method in matrix form. Our method is validated by comparing model predictions to experimental data. In addition, the model provides the space-time evolution of the ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 3 publications
(8 reference statements)
9
56
0
1
Order By: Relevance
“…Verified against measurements by Mateo et al [6], we showed how the resulting change in bandwidth with fiber length is strongly affected by mode coupling typical of POFs.…”
Section: Introductionsupporting
confidence: 74%
“…Verified against measurements by Mateo et al [6], we showed how the resulting change in bandwidth with fiber length is strongly affected by mode coupling typical of POFs.…”
Section: Introductionsupporting
confidence: 74%
“…In recent works, we proposed a matrix framework to model light propagation in POFs where fiber attenuation and diffusion effects are described using the propagation matrix [14]. This matrix that is defined for each temporal frequency gives the amount of power in a given angle that is transferred to another angle.…”
Section: Generalized Connector Matrixmentioning
confidence: 99%
“…Second, following this approach, we obtain an analytical description of the relative change in power as a function of the angle for different misalignments. Then, we present the model results for combined longitudinal and transversal misalignments and show how the angulardependent power loss caused by misalignments can be very useful to evaluate their impact over transmission properties in the context of the matrix propagation model [14]. Finally, we summarize our proposal focusing on its flexibility to accommodate other fibers, effects and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…(2) which is obtained by Gloge [2], two numerical approaches for solving the time-dependent power flow Eq. (1) have been reported recently: implicit finite--difference method (Crank-Nicholson scheme) by Breyer et al [3] and explicit finite-difference method in the matrix form by Mateo et al [5]. In this work using Gloge's analytical solution of (2), we calculate the impulse response of the SI POF investigated earlier by Breyer et al [3] and compare our analytical results with their numerical results.…”
Section: Time-dependent Power Flow Equationmentioning
confidence: 77%
“…Finally, the power exiting the fiber at the highest angles (tails of the Gaussian launch beam) has the longest delays. This suggests an efficient means of improving the fiber capability by spatial filtering-out of the tail at higher angles [5]. As most power is confined within the range of lower angles, such filtering-out of the power at the highest angles will cause only a small power loss while producing a narrower overall impulse response.…”
Section: Resultsmentioning
confidence: 99%